Sixty-five years of northern anchovy population studies in the southern California Current: a review and suggestion for sensible management. (12th February 2020) - Sydeman, William J; Dedman, Simon; García-Reyes, Marisol; Thompson, Sarah Ann; Thayer, Julie A; Bakun, Andrew; MacCall, Alec D
Abstract: The central stock of northern anchovy (CSNA; Engraulis mordax ), the most abundant small pelagic fish in the southern California Current, is key to ecosystem functions. We review drivers of its population dynamics in relation to management. Springtime upwelling intensity lagged by 2 years co-varied positively with CSNA biomass, as did the abundance of Pacific sardine ( Sardinops sagax ; weakly negative). CSNA population dynamics indicate the need for a multi-species stock assessment, but given serious challenges with modelling population collapse and recovery dynamics, and its moderate fisheries, we suggest that sensible management could be a simple 2-tier harvest control rule designed to emphasize the key trophic role of CSNA in the ecosystem while maintaining moderate socio-economic services. We recommend a monitoring fishery of no more than 5 KMT year −1 split between central and southern California when the stock falls below the long-term median abundance estimate of 380 KMT across the California portion of its range, and a catch limit of 25 KMT year −1 when the stock is above this reference point. This rule would be precautionary, serving to maintain the most important small pelagic forage in the ecosystem, various fisheries interests, and information streams when the population is in a collapsed state.